A Project Report on Randomized Intrusion Tolerance Asynchronous Services - SACHIN KUMAR SINHA, SOUMAK KUMAR GHOSH, SYED SUFYAN SHER and AHMED MOHIUDDIN (2011)
INTERNAL GUIDE : Annapoorani G EXTERNAL GUIDE : Rajapupha T USN NO : 1MJ07CS069-1MJ07CS087, 1MJ08CS098 and 1MJ0808CS111 CARRIED OUT AT : Mvj College Of Engineering Bangalore-560067 ACC NO : PR1823
Keywords: Tolerance Asynchronous Services